E-novation for competitive advantage in collaborative globalization technologies for emerging e-business strategies - Pattinson, Hugh.; Low, David R., 1962-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2011)
"This book highlights new business products, services, strategies, and philosophies drawn from an emerging collaborative information platform and explores connections between the development of new e-business technologies with consumers, businesses, and links to social and political visions and strategies"--Provided by publisher.
1. Service-dominant logic foundations of E-novation / Stephen L. Vargo and Robert F. Lusch -- 2. E-marketplaces: taxonomy of the new collaborative information platform / Kayvan Miri Lavassani, Bahar Miri Movahedi and Vinod Kumar -- 3. A business model framework for Second Life / Alessia D'Andrea, Fernando Ferri and Patrizia Grifoni -- 4. Defining E-novation / David R. Low and Hugh M. Pattinson -- 5. Defining E-novation in action / Ehsan Ehsani -- 6. Service-dominant logic: toward reframing business for enhanced E-novation / Robert F. Lusch, Stephen L. Vargo and Melissa Archpru Akaka -- 7. E-novation collaboration / Michael Conlin -- 8. Online branding / Jennifer Rowley and David Bird -- 9. E-novation curriculum (communication and education): who should care? / Daphne Freeder -- 10. E-novation customer relationship management / Othman Boujena and Wesley J. Johnston -- 11. E-novation deployment: creating new "spaces" and distribution using E-novation / Stephen Dann -- 12. E-novation and start-up companies / Suresh Sood -- 13. E-novation in large corporations / Michael Conlin -- 14. E-novation program office and roadmap: pathway to achieving E-novation in government / Suresh Sood and Kevin Jin -- 15. Next generation collaborative information platforms / Hugh M. Pattinson and David R. Low.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed July 18, 2011).
Keywords: Electronic commerce; Technological innovations; Collaborative globalization; Collaborative information platform; E-business strategies; E-marketplaces; E-novation collaboration; E-novation deployment; E-novation in government; E-novation in large corporations; Online branding; Service-dominant logic; Electronic books